Understanding Skintific Product Customer Loyalty Based on Sensory Experience, Value Perception and Satisfaction - Murna Wardayanti; Wira Bharata (Program MM Universitas Surabaya, 2025)
Purpose: This research seeks to explore the influence of sensory experiences and perceived value on consumer satisfaction and loyalty regarding Skintific products among Samarinda's residents. Method: This study employs a quantitative approach with associative methods. The population consists of Samarinda residents who use Skintific products, with a total of 130 respondents. The sampling technique used is non-probability sampling, specifically the accidental sampling method. Result: The findings indicate that sensory experience has a significant impact on both customer satisfaction and loyalty. However, perceived value significantly affects customer satisfaction but does not have a notable influence on customer loyalty. However, through an indirect connection, perceived value can impact loyalty via satisfaction. Consequently, the results suggest that customer satisfaction serves a crucial function as a mediator in linking perceived value with customer loyalty. Therefore, initiatives to boost perceived value should align with efforts to enhance customer satisfaction in order to build enduring loyalty.